Intrinsic thermal stability enhancement in n-type Mg3Sb2 thermoelectrics toward practical applications. (1st April 2023) - Liang, Zhongxin; Jian, Miaomiao; Xu, Congcong; Lei, Bing-Hua; Shi, Xin; Shang, Hongjing; Song, Shaowei; Ren, Wuyang; Ding, Fazhu; Singh, David J.; Feng, Zhenzhen; Ren, Zhifeng
Abstract: Mg3 Sb2 -based Zintl compounds show great promise for thermoelectric power generation due to their favorable properties, such as high thermoelectric performance over a wide range of temperatures, low cost, and mechanical robustness. However, their practical application is severely impeded by the low thermal stability induced by significant Mg loss at elevated temperatures. Here, with the goal to intrinsically enhance the thermal stability of Mg3 Sb2 -based materials, a strategy of Mn doping at the Mg site is investigated and is found to be effective. In addition to having a high average zT, Mn-doped Mg3 Sb1.5 Bi0.5 exhibits negligible variation in electrical performance throughout a 40-hour continuous electrical properties measurement at 673 K. Microstructure and composition analyses verify the high structural stability of the Mn-doped sample following the long-term in situ measurement. Density functional theory (DFT) calculations show that the enhanced thermal stability of the Mn-doped compound results from the stronger bonding between Mn and Mg atoms in comparison to the Mg-Mg bonds, which can significantly suppress the formation of Mg vacancies. This study demonstrates a novel approach to the development of reliable thermoelectric materials with both a high zT and intrinsically improved thermal stability for applications. Graphical abstract: Image, graphical abstract